Managing the discontent of the losers redux: A future of authoritarian neoliberalism or social capitalism? - Mark Setterfield (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
Neoliberalism eviscerated the value-sharing ethos of the post-war Golden Age (1945-73), seeking to maintain social cohesion in civil society by 'managing the discontent of the losers'. This involved reconciling working households to the realities of the neoliberal labour market by means of coercion, distraction, and debt accumulation - the latter serving to limit the growth of consumption inequality in the face of burgeoning income inequality. The global financial crisis (GFC) and Great Recession undermined the process of household debt accumulation, creating a crisis of neoliberal accumulation. Key to the institutional renewal required to address this crisis will be managing the discontent of the losers inherited from the neoliberal era. One possibility is Authoritarian Neoliberalism, based on increasingly illiberal amplification of the 'coerce and distract' elements inherited from the Neoliberal Boom (1990-2007). The only viable alternative is Social Capitalism. This involves a renewal of social democracy that manages the discontent of the losers at its source, by creating inclusive and sustainable growth that both reduces the need and desire for illiberalism in the sphere of civil society.
Keywords: E21; B51; B52; P16; 330; Social structure of accumulation; capital-citizen accord; household debt; inequality; populism